Characterization of conservation units of the Central-West region of Brazil - Farinha, Maycon Jorge Ulisses Saraia; Bernardo, Luciana Virginia Mario; Souza, Vanderson Aparecido de; Silva, Luciana Ferreira da (Multitemas, 2018)
The objective of this research is to characterize the existing conservation units in the Central-West region of Brazil, considering some aspects of the Presidential Decree No. 4.340/2002, which provides the necessary guidelines for the creation of conservation units. The choice of this region is due to its diversity of biomes. The deductive method was used for the elaboration of the research, starting with information about the country and sequentially about the chosen region. Even though there is a national registry of conservation units, there is a lack of information on these areas, because it is not filled in completely.